PROFIL DISPOSISI BERPIKIR KRITIS SISWA KELAS XII SMA NEGERI 2 KOTA SUKABUMI - Syifa Isnaeni; Billyardi Billyardi; Setiono Setiono (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the profile of critical thinking disposition of class XII students in one of the state high schools in the City of Sukabumi. The study used a descriptive quantitative approach and a purposive sampling technique to generate 31 students of the population. Written tests applied for collecting critical thinking data. The test consisted of 14 questions of a critical thinking disposition test with a reliability value of 0.79, a standard deviation of 10.93, and a correlation score of 0.65. There were seven indicators of critical thinking disposition include Maturity, Truth-seeking, Analysis, Systematic, Open Mind, Self-confidence, and curiosity. The results showed that the average value of students' critical thinking disposition was 27,.98% indicating that they come into a less category. There might be a need for revising to improve students' critical thinking, which they must have in this 21st century. Therefore, various models or strategies might be applied to help students build their understanding.